Identifying Service Quality Attributes and Measuring Customer Satisfaction of Dhaka-Pabna Route Public Bus Service - Masud-Ul-Hasan, Md.; Rahman, Md. Hasebur; Rana, Masud (Asian Business Review, 2015)
Dhaka is the capital city of Bangladesh. A notable number of people have to go to and return from Dhaka every day. Most of the people use bus service. The situation of Dhaka-Pabna route bus service is not exception of this. Gradually the number of customer as well as service provider is increasing in this route. As a result, the service providers are facing competition to attract and retain customer. Measuring customer satisfaction is very important in attracting and retaining customer. This study was intended to identify service quality attributes in the long route public bus transit service and measure the customer satisfaction by surveying a number of 250 respondents. Finding shows that, overall 13% customers are very satisfied, 48% customers are somewhat satisfied, 32% customers are somewhat dissatisfied and 7% customers are very dissatisfied. Some recommendations are also provided to attract and retain customer.